Electrifying biotrickling filters for the treatment of aquaponics wastewater. (January 2021) - Pous, Narcís; Korth, Benjamin; Osset-Álvarez, Miguel; Balaguer, Maria Dolors; Harnisch, Falk; Puig, Sebastià
Highlights: Non-conductive filling material brought insufficient and uncontrollable N removal. Polarized conductive filling material provided limited but controllable N removal. Mix of non-conductive and polarized conductive material were the most active. The electrified biotrickling filter met the N standards, closing aquaponics loop. Abstract: This work aimed to study the electrification of biotrickling filters by means of Microbial electrochemical technologies (MET) to develop an easy-to-assemble and easy-to-use MET for nitrogen removal without external aeration nor addition of chemicals. Four different designs were tested. The highest ammonium and nitrate removal rates (94 gN·m −3 ·d −1 and 43 gN·m −3 ·d −1, respectively) were reached by combining an aerobic zone with an electrified anoxic zone. The standards of effluent quality suitable for hydroponics were met at low energy cost (8.3 × 10 −2  kWh·gN −1 ). Electrified biotrickling filters are a promising alternative for aquaponics and a potential treatment for organic carbon-deficient ammonium-contaminated waters.